The tailor of Panama - Le Carre, John, 1931-2020 (Coronet Books, 2001)
He is Harry Pendel: Exclusive tailor to Panama’s most powerful men. Informant to British Intelligence. The perfect spy in a country rife with corruption and revolution. What his “handlers” don’t realize is that Harry has a hidden agenda of his own. Deceiving his friends, his wife, and practically himself, he’ll weave a plot so fabulous it exceeds his own vivid imagination. But when events start to spin out of control, Harry is suddenly in over his head—thrown into a lethal maze of politics and espionage, with unthinkable consequences. . . .